Algeria's infrastructure : an economic survey of transportation, communication, and energy resources - Pawera, John C. (New York : Praeger, 1964)
This is the economic survey of transportation, communication, and energy resources of Algeria
Bibliography: p. 232-234.
oo 23/8/18
Loans
Keywords: Transportation; Communication and traffic; Power resources